Application of the Poverty Equivalent Growth Rate (PEGR) Method (Case Study: Household Income Group in South Sulawesi 2016-2018) - Andy Rezky Pratama Syam (Eigen Mathematics Journal, 2022)
The purpose of this study is to analyze pro-poor growth in South Sulawesi Province with an income dimension approach for the classification of urban and rural areas. This study reveals the poverty situation in South Sulawesi and the extent of the growth of the poor population. In addition, an overview of the effects of growth and distribution effects on changes in poverty is also obtained. Using SUSENAS data from South Sulawesi Province from 2016 to 2018, it was found that growth tends to have a greater impact on reducing poverty in rural areas than in urban areas based on the results of the Shapley decomposition. The results of calculating the degree of pro-poor growth with PEGR, show that income growth tends to be trickle-down from 2016 to 2017. The decline in the poverty rate did occur but the benefits of growth received by the poor were proportionally less than the non-poor. Income growth shows pro poor in the period from 2017 to 2018.